2004
DOI: 10.1023/b:cemn.0000012724.79184.b6
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Dopamine Maintains Synchronous Oscillation of Intracellular Calcium in Primary Cultured-Mouse Midbrain Neurons

Abstract: We demonstrated synchronous oscillation of intracellular Ca2+ in cultured-mouse mid-brain neurons. This synchronous oscillation was thought to result from spontaneous and synchronous neural bursts in a synaptic neural network. We also examined the role of endogenous dopamine in neural networks showing synchronous oscillation. Immunocytochemical study revealed a few tyrosine hydroxylase (TH)-positive dopaminergic neurons, and that cultured neurons expressed synaptophysin and synapsin I. Western blot analyses co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Primary cultures of neurons were performed according to a previously reported method (Yasumoto et al, 2004). Fetuses were removed at gestational day 17, and isolated fetal midbrains were cut into small pieces in isolation medium (equal volumes of Dulbecco's Modified Eagle's Medium (DMEM) (Sigma, St. Louis, MO) and Ca 2+ and Mg 2+ -free phosphate-buffered saline (PBS)).…”
Section: Primary Culture Of Neurons From Midbrainmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary cultures of neurons were performed according to a previously reported method (Yasumoto et al, 2004). Fetuses were removed at gestational day 17, and isolated fetal midbrains were cut into small pieces in isolation medium (equal volumes of Dulbecco's Modified Eagle's Medium (DMEM) (Sigma, St. Louis, MO) and Ca 2+ and Mg 2+ -free phosphate-buffered saline (PBS)).…”
Section: Primary Culture Of Neurons From Midbrainmentioning
confidence: 99%
“…We previously reported that primary cultured mouse midbrain neurons burst synchronously and periodically through glutamatergic synapses without any stimulation, and this phenomenon can be visualized as periodic changes in the concentration of intracellular Ca 2+ (synchronous oscillation) (Yasumoto et al, 2004). The cultured midbrain neurons conform their networks step by step according to the days in vitro (DIV) and increase the frequency of spontaneous synchronous oscillation gradually (data not shown).…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, typical agonists of D 1 -like receptors generally activate both the D 1 and D 5 subtypes and elicit multiple signaling responses in mammalian tissues (Neve et al, 2004). Such responses include cascades mediated by adenylyl cyclase , mitogenactivated protein kinase (Zhen et al, 1998), intracellular calcium mobilization (Lezcano and Bergson, 2002;Yasumoto et al, 2004), and phospholipase C (PLC) (Felder et al, 1989;Undie and Friedman, 1990). The PLC response, which is associated with the hydrolysis of phosphatidylinositides (PIs) to release inositol phosphate and diacylglycerol second messengers, is evident in discrete brain regions, including tissues expressing D 1 -like receptors that show relatively negligible functional coupling to adenylyl cyclase (Undie and Friedman, 1990;Montague et al, 2001) and persists when D 1 receptors have been genetically deleted (Friedman et al, 1997) or chemically inactivated (Rosengarten and Friedhoff, 1998;Undie et al, 2000).…”
mentioning
confidence: 99%
“…TTX (1 µM) (Yasumoto et al, 2004), ACPD (5-100 µM), and MCPG (500 µM) (Schwarz et al, 2000), AIDA (100 µM) (Kalda et al, 2000), PHCCC (30 µM (Thornton and Bornstein, 2002), EGLU (300 µM (Marti et al, 2001), PKI(14-22) (0.05-50 mM) (Sluka, 1997), and forskolin (1-30 µM (Akasu and Tokimasa, 1989) were all effective in each study. In many previous researches, AIDA (Aguirre et al, 2001;Meli et al, 2002;Zhou et al, 2001) and PHCCC (Maj et al, 2003;Mao and Wang, 2001a,b) have often used at concentrations lower than 100 or 30 µM, respectively.…”
Section: Chemicalsmentioning
confidence: 95%
“…Primary cultures of cortical neurons were performed according to a previously reported method (Ichikawa et al, 1993;Yasumoto et al, 2004). Fetuses were removed at gestational day 17 and isolated fetal cerebral cortices were cut into small pieces in isolation medium (equal volumes of Dulbecco's Modified Eagle's Medium (DMEM) (Sigma, St. Louis, MO) and Ca 2+ -and Mg 2+ -free phosphate-buffered saline (PBS)).…”
Section: Primary Culture Of Neurons From Cerebral Corticesmentioning
confidence: 99%